Pengaruh kemampuan auditor, skeptisme profesional auditor, teknik audit dan whistleblower terhadap efektivitas pelaksanaan audit investigasi dalam pengungkapan kecurangan - Laras Rahmayani; Kamaliah '; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research was to determine the ability of auditor BPK and BPKP representative of Riau Province. To know the effect of skepticism Professional owned by the auditors in the investigation audit. To determine the implementation of procedures/ techniques of effective investigative audit by the auditors in the fraud disclosure in BPK and BPKP representation in Riau Province. To find out how big a role in the investigation of a whistleblower in the case of an audit investigation.The research methods used in this study include, population in this research is an auditor who works in the Supreme Audit Agency ( BPK ) and the Board of Finance and Development examination (BPKP) representative of Riau province. The sample used in this study is the auditor who worked at BPK and BPKP representative Riau province with special criteria. The method of data analysis used in this research is multiple regression with the help of computers through SPSS 19.0 for Windows .The result of this research in the first hypothesis testing results show that the ability of the Auditor significantly influance the effectiveness of Investigation Audit in Fraud Disclosure. The successful testing of the first hypothesis proved significant. The second hypothesis testing results show that the attitude of the Auditor Professional Skepticism significantly influence the effectiveness of disclosure Audit in Fraud Investigation, meaning that the second hypothesis in this study received. The third hypothesis testing results show that the technique affects audit effectiveness of Investigation Audit in Fraud Disclosure.. This test successfully prove the third hypothesis in this study received. The fourth hypothesis testing results indicate that the role of whistleblower effect on Audit Effectiveness of the Disclosure Fraud Investigation, meaning that the fourth hypothesis in this study states received. Based on the calculation of coefficient of determination ( R2 ) obtained a value of 0,839. This suggests that the effect of independent variables on the dependent 83.90 % and the rest is influenced by other variables that are not included in this research.Keywords: Ability of Auditor , Professional Skepticism of Auditor, Audit Techniques, Whistleblower, Investigation Audit, and Fraud Disclosure.